Arbuscular mycorrhizal fungal community structure following different grazing intensities in an alpine grassland. Issue 5 (18th July 2021) - Li, Qian; Xiang, Xingjia; Du, Yangong; Li, Yikang; Lin, Li; Zhang, Fawei; Guo, Xiaowei; Cao, Guangmin
Abstract: Grazing alters the plant communities, soil properties, and habitat conditions of the alpine grassland. Arbuscular mycorrhizal fungi (AMF) are involved in the nutrient cycling of grassland ecosystems and form a mutual symbiosis with their host plants. Thus, AMF are sensitive to the impact of livestock grazing. However, the effects of grazing intensity on the AMF community composition and the association between AMF and environmental factors, such as soil physicochemical properties, enzyme activity, and glomalin‐related soil proteins, remain unclear. Here, the response of the soil AMF community to grazing intensity gradients (i.e., light, moderate, and heavy grazing) was studied in an alpine grassland on the Qinghai‐Tibet Plateau. The dominant AMF families included Glomeraceae, Gigasporaceae, Claroideoglomeraceae, Diversisporaceae, and Ambisporaceae. Significant shifts in the AMF community composition in response to grazing intensity were found in both surface and subsurface soils. Soil C/N ratio, plant diversity, soil compactness, chitinase activity, aboveground biomass, total N, soil moisture, and NO3 − –N significantly correlated with changes in the AMF community composition. Heavy grazing intensity was associated with the highest AMF alpha diversity, whereas moderate grazing intensity had the lowest AMF alpha diversity in both surface and subsurface soils. Grazing intensity, dominant plants, soil C and N concentrations, and soil compactness were significantly correlated with AMF diversity. These results demonstrated a significant response of the AMF community to grazing intensity, suggesting that plants increase their reliance on AMF symbioses with higher alpha diversity in the heavily degraded alpine grasslands of the Qinghai‐Tibet Plateau. Core Ideas: Grazing alters plant communities, soil properties, and AMF communities. Soil C/N and plant diversity are significantly correlated with AMF communities. Moderate grazing is associated with the lowest belowground AMF alpha diversity. Plants increase their reliance on AMF symbioses in heavily degraded alpine grassland.